Reducing the equity gap in child health care and health system reforms in Latin America - Daniel Maceira; Luisa Brumana; Joaquín González Aleman (BMC, 2022)
Abstract Background During the first decade of the current century, Latin American countries have shown high and consistent economic growth rates, increasing per capita GDP and reducing poverty. Social indicators improved in even the poorest and least equitable countries in the region. In terms of health care results, marked advances were made in infant mortality rates. Objective The aim of this paper is to identify if decreasing poverty rates in Latin America and the Caribbean during the first decade of the century have had an effect on health inequality, specifically by reducing the health care equity gap and, if so, whether that trend and its effects were distributed evenly at the sub-national level. Methods Basic statistical tools were applied to national and sub-national administrative data for eleven Latin American countries (Argentina, Belize, Bolivia, Brazil, Colombia, Dominican Republic, El Salvador, Mexico, Nicaragua, Peru, and Uruguay) to compare the evolution of a set of social determinants with a classic health care outcome, such infant mortality) during the period 1995-2012. This document proposes a set of indicators to analyze relative evolution of results and convergence to equity, and to discuss general trends in health care reforms across the region. Results The document shows a correspondence between poverty reduction, and improvement of health care indicators at a regional level, though national differences persist. In some cases, like Brazil and Peru, the reduction in infant mortality rates is coupled with significant movements towards health equity. This trend is different in Bolivia, where the drop in poverty is not followed by better outcomes in poor departments. At the same, results are not necessarily linked to health systems organization and/or specific reforms. For instance, both Brazil and Peru pursue in applying decentralized solutions, although the incentive mechanisms are quite different: the former has a supply side structure at the public provision level while the latter has implemented mixed payment systems. Conclusion While some of the same instruments and measures of effectiveness in health care reforms appear across the region, specific impact evaluations should be performed. To reduce the equity gap in Latin America requires not only major improvements in social determinants but also the design and implementation of sound institutional policy and more robust regulatory frameworks (institutional determinants) so that more resources yield better practices.